Characterization and fungistatic activity of Eucalyptus globulus leaf extract mediated phytosynthesized silver nanoparticles - Kumar M.P., Thejesh; Garampalli, Rajkumar H. (International Journal of Scientific Research in Biological Sciences, 2019)
In the present study silver nanoparticles were synthesized through green approach using leaf extract of Eucalyptus globules and confirmed by change in colour of reaction mixture, the peak obtained at 425nm in UV-visible spectroscopic study and characterized by XRD, DLS, SEM, EDAX and FTIR for their structure, size, shape and possible biomolecules responsible for the reduction of silver ion to silver nanoparticles. XRD spectrum confirmed the particles were face centered cubic in nature with an average particle size of 25nm which is in agreement with DLS data (25.31nm). SEM images of nanoparticles revealed the spherical shape of particles and the Energy Dispersive X-ray analysis (EDAX) confirmed the significant presence of elemental silver. Synthesized silver nanoparticle showed good fungicidal activity against Didymella bryoniae, Fusarium oxysporum, Aspergillus flavus and Rhizoctonia solani.